The Characteristics of Analogical Reasoning of Senior High School Students in Solving Geometry Problems - Ahmad Rohman; Ali Shodikin (Phenomenon : Jurnal Pendidikan MIPA, 2025)
When students solve two geometry problems with almost the same concept, students try to interpret and understand the information and the problem. Because students can choose the plans or steps to tackle the problem, this step is crucial. When thinking about the relationship between things and their integration, analog reasoning is required. This study attempts to describe the characteristics of different types of analogical reasoning that 10th-grade students use while solving geometry problems based on the phases of analogy. In this descriptive qualitative study design, to solve geometry issues, twenty-four students had to work their way from the source problem to the target problem. Three types of analogical reasoning were identified: misleading, incomplete, and structural analogy. Each type reflects different levels of understanding and reasoning stages in solving geometry problems. First, the misleading analogy type, in which students perform inaccurate geometry interpretation and important information in the problem is not considered; second, incomplete analogy, in which students provide appropriate geometry representation, but there are still errors in understanding part of the problem; third, structural analogy type, in which students perform geometry representation with comprehensive conceptual understanding. Therefore, teachers should encourage students to build a deeper understanding and find meaningful conceptual connections through the conceptualization of geometry.